COMMUNITY STRUCTURE AND CARBON STOCK POTENTIAL OF MANGROVE ECOSYSTEMS IN THE COASTAL AREA OF BANGKO SUBDISTRICT, ROKAN HILIR REGENCY - Siti Komariah; Deni Efizon; Syafruddin Nasution (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The objectives of this study were to analyze mangrove community structure, estimate carbon storage and CO₂ sequestration potential, assess the economic value of CO₂ sequestration, and formulate management strategies for mangrove forests in the coastal area of Bangko Subdistrict, Rokan Hilir Regency. This research was conducted in October 2024 in the coastal area of Bangko Subdistrict, Rokan Hilir Regency, Riau Province. The method applied was a survey-based approach. Sampling stations were determined using purposive sampling. Mangrove community structure data were collected using 10 m × 10 m quadrat transect plots. A total of six observation stations were established, with three plots per transect. The potential carbon stock of the mangrove ecosystem was calculated based on carbon content from trunk biomass, roots, litter, and sediment. Biomass carbon estimation utilized species-specific allometric equations. The results recorded seven mangrove species: Avicennia alba, A. eucalyptifolia, A. lanata, Bruguiera parviflora, Rhizophora apiculata, R. mucronata, and Sonneratia alba. The highest relative density and the highest relative frequency were recorded for A.alba at Station I (75%) and Station II (42.86%). The highest relative dominance was recorded for Sonneratia alba at Station V (52.05%). The highest Importance Value Index (IVI) was observed for Avicennia alba at Station I (151.15%). The mangrove ecosystem in the coastal area of Bangko Subdistrict has an average carbon stock potential of 382.37 tons/ha, with an estimated CO₂ sequestration potential of 1,277.21 tons per hectare, totalling 15,893,618.87 tons. The estimated average economic value of carbon sequestration is IDR 1,081,274,726/ha, equivalent to IDR 13,455,438,919,367. Sustainable mangrove ecosystem management as a contribution to climate change mitigation can be implemented through the following strategies: ecosystem rehabilitation and protection, strengthening governance and law enforcement, community empowerment and alternative livelihood development, increased awareness and cross-sectoral coordination, and continuous monitoring and research